KONTRIBUSI INFLASI, SUKU BUNGA, KURS, PRODUK DOMESTIK BRUTO TERHADAP HARGA SAHAM KELOMPOK JAKARTA ISLAMIC INDEX DI INDONESIA PERIODE 2007-2015 (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
Abstract: This study aimed to explain infation, interest rate, exchange rate, and gross domestic product that affect stock price. The determination of sample using saturated sampling technique. This study is using sample from 30 companies listed on JII. Data analysis using multiple liner regression. The result of this study showed that independent variables infation, interest rate, exchange rates, gross domestic product signifcant simultaneously effect on the dependent variable stock price. Partially, Infation negative and does not give the signifcant effect toward the stock price. Interest Rate and Exchange Rate positive and does not give the signifcant effect toward the stock price. Gross Domestic Product gives the positive and signifcant effect toward the stock price.Keywords: infation, interest rates, exchange rates, gross domestic product, the stock price